Kualitas Pelayanan, Citra Merek Dan Persepsi Harga Terhadap Kepuasan Pelanggan Di Gallery Restoran Hotel Redtop Jakarta - Ivan Novianto; Bonifasius MH Nainggolan (LPPM Universitas Asa Indonesia, 2023)
The purpose of this research is to determine the influence of service quality, brand image and price on customer satisfaction. The data analysis method used is multiple linear regression analysis using SPSS 26 software to process the data. This research uses quantitative methods, by distributing questionnaires through surveys given to customers. In this research, a purposive sampling method was used (randomly) with a total of 80 customers who made purchases at the Gallery Restaurant Redtop Hotel Jakarta. The research results show that service quality (X1) has no effect on customer satisfaction, while brand image (X2) and price (X3) partially have a positive effect on customer satisfaction (Y). The research results also show that these three variables simultaneously have a positive effect on customer satisfaction.